Pim Valkenberg and Anthony Cirelli, Eds. Nostra Aetate: Celebrating 50 Years of the Catholic Church’s Dialogue with Jews and Muslims - Morgan, Fred (Studies in Christian-Jewish Relations, 2018)
No abstract is available.